INVESTIGATION ON SECONDARY METABOLITES IN CISSUS QUADRANGULARIS LINN. - NATHAR VARSHA N.,; YATOO GHULAM M., (International Journal of Pharma and Bio Sciences, 2015)
Cissus quadrangularis L., of family Vitaceae, commonly known as ‘Hadjod’ is having a lot of medicinal importance. The active compounds isolated from this plant are considered to be very effective in various treatments such as osteoporosis, asthma, cough, hemorrhoids and gonorrhea. This paper represents the phytochemical analysis of Cissus quadrangularis L. The results obtained showed that the secondary metabolites were present in all the plant parts. Petroleum ether proved better for extraction. Saponins are high in petroleum ether extract of root, stem and leaf. The quantitative estimation of alkaloids is higher in stem and leaves i.e. 103.99 and 78.72 mg/100 gm respectively and phenols is higher in stem (0.322mg/100gm) and lower in roots (0.016mg/100gm).